El Software Libre Como una Herramienta para el Emprendimiento de Base Tecnológica en el Departamento del Meta – por Jorge García y María Paula Estupiñan (2014)
The use of free software in different productive sectors, has generated a great opportunity for companies to adapt business models and policies in the environments of technological development and competitiveness, in order to improve productivity and achieve competitive advantages that allow them interact effectively in national and international market. However, the State following the recommendations set forth by UNESCO, where it promotes free software to boost the so-called open knowledge revolution has changed the paradigms of growth in most business sectors. (Escalante, 2009) This statement is evidenced by Rappa (2001) and Rayport (1999) to indicate that due to the variety of technological tools for software development and the absence of production schemes oriented free software, no defined conditions of existing business models, therefore, companies engaged in this activity unknown opportunities in the domestic industry of free software (INSL). According Escalante & García, business models from the processing in the application development environment, is considered one of the most important issues for the business sector, because new developments in open source have transformed the traditional way do business even classifying non commercial model still under study; however, the real concern of the software industry is the evidence of how little has chang